Tackler characteristics associated with tackle performance in rugby union - Hendricks, S.; Matthews, B.; Roode, B.; Lambert, M. (European Journal of Sport Science, 2014)
Tackling is an important skill for performance in rugby, yet little has been reported on tackler characteristics and its relationship to performance in competition. The aim of this study was to identify tackler characteristics and its association with tackle performance in matches. Eighteen matches of the 2010 Super 14 were analysed, which amounted to 2092 coded tackles. Tackler characteristics such as head position - in motion, up and forward, type of tackle - shoulder tackler, arm tackle or ball-carrier fend - absent, moderate, strong and leg drive-absent, moderate, strong or shoulder usage were coded and associated with tackle outcomes. Relative risk ratio (RRR), the ratio of the probability of an outcome occurring when a characteristic was observed (versus the non-observed characteristic) was determined using multinomial logistic regression. Having the head in motion decreased the tackler's chances of a successful tackle (RRR 2.24, 95% CI 1.72-2.92, p < 0.001) relative to an up and forward head position. Ball-carriers using a fend significantly decreased the tackler's probability of success (moderate fend RRR 2.97, 95% CI 2.04-4.31, p < 0.001). Moderate leg drive (RRR 0.36, 95% CI 0.26-0.50, p < 0.001) by the tackler increased the likelihood of tackle success. Head up and forward, counter-acting the ball-carrier fend, shoulder tackles targeted at the ball-carrier mid-torso, using the arms to wrap or pull, and leg driving were key tackler characteristics associated with positive tackle outcome in matches. Based on these findings, it is recommended that these technical characteristics are emphasised and incorporated into training to effectively prepare tacklers for competition.